Barriers and facilitators to discussing HPV with head and neck cancer patients: A qualitative study using the theoretical domains framework. Issue 12 (December 2020) - O'Connor, M.; Waller, J.; Gallagher, P.; O'Donovan, B.; Clarke, N.; Keogh, I.; MacCarthy, D.; O'Sullivan, E.; Timon, C.; Martin, C.; O'Leary, J.; Sharp, L.
Highlights: HCPs have mixed views about HPV discussions which are increasing part of HNC patient care. TDF provided a detailed picture of barriers and facilitators to HPV discussions. Confidence in having HPV discussions varied and was linked to HCPs' HPV knowledge. Lack of HPV knowledge linked to two TDF domains belief about capabilities ; social/professional role and identity . Gaps in HPV communication literature - interventions to support HCPs in HPV discussions needed. Abstract: Objective: The incidence of human papillomavirus-associated head and neck cancers (HPV-HNC) is increasing worldwide. Research in other clinical contexts has shown that healthcare professionals (HCPs) can find discussing HPV with patients challenging. However, limited research has been conducted in HNC. This study aimed to investigate barriers and facilitators to, discussing HPV among HCPs caring for patients with HNC in Ireland. Methods: Semi-structured telephone/face-to-face interviews were conducted with HCPs. Barriers and facilitators to discussing HPV with patients were identified using the Theoretical Domains Framework (TDF). Results: 20 HCPs (8 clinicians, 3 nurses, 9 allied healthcare professionals) were interviewed. Barriers to discussing HPV included professionals' lack of HPV knowledge, difficulties in talking about sexual issues with patients and lack of privacy to discuss HPV in busy clinic settings. Facilitators included increasing public and patient awareness of the link between HPV and HNC and professional education and skills development. Conclusions: This is the first theoretically informed study to identify barriers and facilitators to discussing HPV with HNC patients. HCPs consider HPV discussions to be an essential part of HNC patient care. Practice implications: Understanding the issues associated with patient-provider HPV communication will help develop effective interventions to support HCPs in their HPV discussions.